Data Management Technologies and Applications : Third International Conference, DATA 2014, Vienna, Austria, August 29-31, 2014, revised selected papers /: Third International Conference, DATA 2014, Vienna, Austria, August 29-31, 2014, revised selected papers. (2015) - Unknown
No abstract available